Plan de inversión para la creación de una nueva línea de prestación de servicio con prendas de oro en la fundación “Espoir”, cantón Quevedo Año 2014. - Vaca Chanatasig, Verónica Katherine (2015)
The present research, it takes in order to perform INVESTMENT PLAN FOR THE CREATION OF A NEW ONLINE SERVICE DELIVERY WITH GOLD CLOTHING FOUNDATION "Espoir" Quevedo Canton. This Legal research is divided into six chapters. In the first chapter, the main part for understanding the problem and the effect was treated, it was necessary to hypothesize that the solution to the problem was in compliance with the hypothesis in research. The second chapter refers to the theoretical framework, aspects: referential, conceptual and legal. In the third chapter the methodology used in the research described in point; the methods used, the types of research, population, sample techniques and instruments used in data collection. In the fourth chapter the hypothesis is tested through the research results obtained by surveying residents of Canton Quevedo, about the Foundation and also support the proposal of this research. After the proposal is done based on the objectives, description of 'propuesta, beneficiaries and social impact, etc. The fifth chapter describes the conclusions and recommendations….